A COMPREHENSIVE ANALYSIS OF SOCIAL ECONOMIC LAW: EVOLUTION, CHALLENGES AND PROSPECTS - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2024)
This comprehensive analysis investigates the evolution, challenges and prospects of Social Economic Law in the context of evolving social and economic dynamics. The research highlights how the principles of social and economic justice in law are implemented to deal with the complexities of modern society, as well as to adjust to global changes such as digitalisation and climate change. In addition, it identifies key challenges that must be overcome to maintain the relevance and effectiveness of regulation, and explores opportunities to make law a tool for sustainable and inclusive economic and social transformation. Emphasis is placed on the importance of policy innovation and cross-sector collaboration to ensure equitable development. With this approach, Social Economic Law is expected to serve as a solid pillar to achieve sustainable prosperity for all.